1991
DOI: 10.1002/1097-0142(19910515)67:10<2467::aid-cncr2820671013>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-125 interstitial implants as salvage therapy for recurrent gynecologic malignancies

Abstract: Twenty-one patients with the diagnosis of recurrent gynecologic pelvic malignancy from various primary sites were treated with iodine-125 (I-125) interstitial implants. Eighteen of these patients had been treated with a combination of surgery and radiation therapy for their primary malignancies and 90% had responded. Seventy-five percent had complete local responses. The overall survival time, volume-response relationship, and complications are discussed and the radioresponse of various histologic types is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
12
0
4
Order By: Relevance
“…Sharma et al . [19] emphasized that there was no significant relationship between the tumor volume and the incidence of major complications, however in their study, the volume of the tumors in all the patients was large, > 10 cm 3 , except in one case. We could not identify any factors that significantly influenced the risk of major complications in our present study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Sharma et al . [19] emphasized that there was no significant relationship between the tumor volume and the incidence of major complications, however in their study, the volume of the tumors in all the patients was large, > 10 cm 3 , except in one case. We could not identify any factors that significantly influenced the risk of major complications in our present study.…”
Section: Discussionmentioning
confidence: 85%
“…Success of re-irradiation for recurrent gynecologic cancer has also been shown to be limited by the significant morbidity, and only marginal success [1719]. In stringently selected patients, however, a few studies have demonstrated some success with re-irradiation using permanent interstitial brachytherapy (ISBT) [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…During the preceding decade, Sharma and coworkers from Loyola University Medical Center provided a further testament to the efficacy of 125 I interstitial implants in the management of recurrent gynecologic cancer (38). The investigators treated 21 women with pelvic recurrences with 125 I interstitial implants to a total dose of 4600 cGy to 25,900 cGy.…”
Section: Discussionmentioning
confidence: 99%
“…Każda forma powtórnej radioterapii wiąże się z wysokim ryzykiem powikłań popromiennych, głównie ze strony jelit, odbytnicy i pęcherza moczowego (perforacje, przetoki, krwawienia z poszerzonych naczyń krwionośnych odbytnicy, zarośnięcie pochwy, zwłóknienie moczowodów). W ubiegłym wieku powtórna radioterapia w nawrotach nowotworów narządu rodnego wiązała się ze statystycznie istotnym wzrostem śmiertelności i odsetkiem powikłań na poziomie 5,3-35% (15)(16)(17) . Niemniej Sharma i wsp.…”
Section: Radioterapia Z Wykorzystaniem Wiązek Zewnętrznychunclassified